Mild behavioral impairment as a predictor of cognitive functioning in older adults. (27th March 2021) - Rouse, Hillary J.; Small, Brent J.; Schinka, John A.; Loewenstein, David A.; Duara, Ranjan; Potter, Huntington
ABSTRACT: Objective: To assess the influence of mild behavioral impairment (MBI) on the cognitive performance of older adults who are cognitively healthy or have mild cognitive impairment (MCI). Methods: Secondary data analysis of a sample ( n = 497) of older adults from the Florida Alzheimer's Disease Research Center who were either cognitively healthy ( n = 285) or diagnosed with MCI ( n = 212). Over half of the sample ( n = 255) met the operationalized diagnostic criteria for MBI. Cognitive domains of executive function, attention, short-term memory, and episodic memory were assessed using a battery of neuropsychological tests. Results: Older adults with MBI performed worse on tasks of executive function, attention, and episodic memory compared to those without MBI. A significant interaction revealed that persons with MBI and MCI performed worse on tasks of episodic memory compared to individuals with only MCI, but no significant differences were found in performance in cognitively healthy older adults with or without MBI on this cognitive domain. As expected, cognitively healthy older adults performed better than individuals with MCI on every domain of cognition. Conclusions: The present study found evidence that independent of cognitive status, individuals with MBI performed worse on tests of executive function, attention, and episodic memory than individuals without MBI. Additionally, those with MCI and MBI perform significantly worse on episodic memory tasks than individuals with only MCI. These results provide support for a unique cognitive phenotype associated with MBI and highlight the necessity for assessing both cognitive and behavioral symptoms.